The prevalence of foot pain and its associated factors among Saudi school teachers in Abha sector, Saudi Arabia - Turki A Alqahtani (Journal of Family Medicine and Primary Care, 2020)
Background: The heel is the prominence at the posterior end of the foot. It is based on the projection of one bone, the calcaneus or heel bone, behind the articulation of the bones of the lower leg. Foot pain is not rare finding in the general population, particularly in older adults. The prevalence in adults ages ≥18 year's ranges from 17 to 24%. Heel pain is a general term used to describe pain and discomfort felt anywhere in or around the rear of the foot. This study aimed to estimate the prevalence of heel and foot pain and their determinants among teachers in Abha sector. Methodology: A deceptive cross-sectional approach was applied for the current research. All accessible teachers working in governmental and private schools in Abha sector. To be included, teachers should be teaching but not in administrative positions, free of musculoskeletal disorders due to causes other than teaching. Teachers with foot congenital anomalies, newly employed teachers. A self-administered questionnaire was personally distributed to included school teachers in Abha sector. Questionnaires were distributed and collected on second day after being filled by teachers. Posterior HP health Survey questionnaire was used to assess foot and foot pain. Results: The study included 1,439 teachers from different districts of Abha sector with their ages ranged from 24 to 60 years old with mean age of 41 ± 9 years. Female teachers constituted 72.8% of the sample and teachers' weight ranged from 45 to 185 kg with mean weight of 76.6 ± 18.2 kg. Exact of 85.5% of the teachers had foot pain during the last 12 months. Foot pain was mild among 17.3% of the teachers with foot pain and severe among 25.5% of them. Low back pain was recorded among 81% of the teachers followed with knee pain (62%), neck pain (58%), shoulder pain (55%), and wrist pain (28%). Conclusions and Recommendations: In conclusion, the study revealed that majority of teachers complained of foot pain. The pain was moderate especially after long standing. The pain was more among old aged teachers with high load of teaching sessions. The pain altered the traditional daily activities among majority of teachers but very few number who asked for medical consultation.